2015
DOI: 10.1080/15710882.2015.1091894
|View full text |Cite
|
Sign up to set email alerts
|

Empirical investigation of the impact of using co-design methods when generating proposals for sustainable travel solutions

Abstract: This paper presents an empirical comparison of idea generation within the context of reducing the number of single occupancy car journeys to and from a UK university campus. Separate co-design and consultative groups were matched with respect to 1) creativity when problem solving, 2) normal commuting mode and 3) intention to adopt sustainable behaviours. The co-design group generated a significantly greater number of innovative ideas than the consultative group (using an email based methodology); however this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…Additional research will focus on the consumer acceptance of 3D Body Scanning to lead to greater acceptance of the technology in the high street retailers. Also, research must focus on 3D Body Scanning as a service to be designed for non-expert fashion consumers with associated profitable business models; possibly through co-design methodologies [42].…”
Section: Resultsmentioning
confidence: 99%
“…Additional research will focus on the consumer acceptance of 3D Body Scanning to lead to greater acceptance of the technology in the high street retailers. Also, research must focus on 3D Body Scanning as a service to be designed for non-expert fashion consumers with associated profitable business models; possibly through co-design methodologies [42].…”
Section: Resultsmentioning
confidence: 99%
“…This is because it provides a perspicuous environment to practically understand what participants can add to the design, and to explore problems unforeseen by the architects (Luck, 2012). It has been suggested that designers create more innovative concepts when working within a participatory environment (Mitchell et al, 2015;Trischler et al, 2018). Furthermore, Bossen et al (2010) suggest that the benefits of PD exceed the enhancement of a product or an environment, as it benefits participants by empowering them through engagement and making their voices heard.…”
Section: Participatory Design (Pd)mentioning
confidence: 99%
“…The pragmatic reason accentuates that participation of non-designers increases the quality, applicability and usability of the designs (Bradwell & Marr, 2008;Carroll & Rosson, 2007;Hyysalo & Johnson, 2015;Kristensson & Magnusson, 2010;Lundström, Savolainen, & Kostiainen, 2016;Steen, 2011). The innovativeness-related reason highlights that participation of non-designers increases the amount of and innovativeness of ideas and design outcomes (Kristensson, Magnusson, & Matthing, 2002;Mitchell, Ross, May, Sims, & Parker, 2016). Finally, the commercial reason emphasizes that participation of non-designers, especially of the future customers, strengthens the brand, builds customer loyalty and, ultimately, increases competitiveness and revenue of the organization (Kristensson et al, 2002;Sanders & Stappers, 2008;Steen, Manschot, & De Koning, 2011;Vargo & Lusch, 2004).…”
Section: Figure 1 Spectrum Of Non-designer Involvement In Design Promentioning
confidence: 99%